Segmentación de consumidores de cerveza de la empresa Backus y Johnston S.A.A. en el distrito Trujillo - Otiniano Juárez, Elluz Marisela (2019)
This study aims to determine the segmentation of beer consumers of the Company Backus and Johnston S.A.A. in the district of Trujillo in the year 2018; for which, a survey was applied to a sample representative of 196 settlers selected at random in their homes, using two questionnaires, which collected the demographic characteristics of the respondent and their preference over the product. It was determined that there are two segments of consumers, the experimenters and the winners. The Experimenters are characterized by consuming the company's beer more frequently, since 67% do it once a month or less, and 78% prefer to do it at home or at the bar, while 22% also do it at home. Do in restaurants, open spaces or others; the most preferred brand is Pilsen Trujillo 47%, but 53% also consume Pilsen Callao, Cusqueña or Cristal; Regarding the format, 53% prefer to consume in normal, but 36% also choose individual, cans, large bottles or they are indifferent. For its part, the segment of the Achievers do not consume beer very often, 72% do it once a month or less, 72% prefer to do it at bar, choosing the Pilsen Trujillo 48% or Cusqueña brands 36%.; as for the format they prefer the normal bottle 48%. So the target segment of consumers is the Experimenters, because they consume beer more often, varying both in place, as the brand and the format of its presentation. Finally, the study allows us to know in figures, which is the most consumed brand by the two consumer segments, and it is most important demographic characteristics, with this, it acquires an advantage over the competition in the beer market